Boris Godunov in the Art of the Great Reforms Period: Paradoxes of Representations - Chernysheva, Maria A.; Khodorkovskaya, Elena S. (Actual Problems of Theory and History of Art, 2020)
At the turn of the 1860s and 1870s, forty years after the publication of Pushkin’s “Boris Godunov”, the image of this tsar attracted the attention of the Russian public again. In 1866, the censorship banon the theatrical production of Pushkin’s play was lifted and in 1870, the tragedy was first staged. In 1869, Modest Mussorgsky completed the first version of his “Boris Godunov”. In 1870, Alexey Tolstoy published the final part of his historical trilogy, the tragedy “Tsar Boris” (staged in 1881). Previously, there have not been any purposeful attempts to correlate the way Godunov was depicted in opera and literature with his representation in painting and graphics of the 19th century; these representations themselves remain little studied. We see the value of our work in filling this gap. The article traces Boris Godunov’s iconography through the epochs of Nicholas I and Alexander II. It has been discovered that there existed a composition by Vyacheslav Schwarz “The Death of Boris Godunov”, which was not mentioned in the literature on the artist before. The interpretation of Godunov’s character given by Nikolai Ge in his sketch “Tsar Boris and Tsarina Marfa” (1873–1874) was the closest visual one to those by Pushkin and Mussorgsky. It is also noted that in Russian painting and graphics of the period it is unthinkable to find something corresponding to the Kromïscene, which defined the finale of Mussorgsky’s opera (when it was first staged in 1874) and became the unprecedentedly expressive representation of a Russian rebellion.